Evaluating sustainable urban development using urban metabolism indicators in urban design - Song, Yan. Autor; Gil, Jorge. Autor; Wandl, Alexander. Autor; Timmeren, Arjan van. Autor (IGiPZ PAN, 2018)
Urban metabolism is a multi-disciplinary approach to qualitatively and quantitatively evaluate resource flows in urban systems, which aims to provide important insights into the dynamics of cities to make them more ecologically responsible. It has been also introduced into the urban design domain, however most of the attempts concern only tracking of energy and/or material flows to reduce environmental impacts by redesigning closed loops in a specific area. The hypothesis of this paper is that the concept of urban metabolism, and its indicators, could play an important role in advancing the science and practice related to sustainability in urban design and development. At the moment, however we lack indicators to support evaluation of urban design related decisions from the perspective of urban metabolism. The aim of this paper is to explore the application of urban metabolism indicators in urban design based on their characteristics. It reviews development periods of the concept and analytical models of urban metabolism, in order to identify crucial urban metabolism indicators for urban design. Next, these urban metabolism indicators are classified regarding type of analytical model, accounting method, indicator type, and indicator level. Finally, several suggestions are offered on how to integrate urban metabolism indicators into urban design. In addition, directions for future research on the topic are discussed.
29 cm
Keywords: urban metabokism indicator; sustainable urban development; urban design